The causes of new-onset epilepsy and seizures in the elderly - Liu S (Dove Medical Press, 2016)
Shasha Liu,1 Weihua Yu,2 Yang Lü1 1Department of Geriatrics, The First Affiliated Hospital of Chongqing Medical University, 2Department of Anatomy, Institute of Neuroscience, Chongqing Medical University, Chongqing, People’s Republic of China Abstract: With increasing age, the prevalence and incidence of epilepsy and seizures increases correspondingly. New-onset epilepsy in elderly people often has underlying etiology, including cerebrovascular diseases, primary neuron degenerative disorders, intracerebral tumors, and traumatic head injury. In addition, an acute symptomatic seizure cannot be called epilepsy, which manifests usually as a common symptom secondary to metabolic or toxicity factors in older people. In this review, we have mainly focused on the causes of new-onset epilepsy and seizures in elderly people. This knowledge will certainly help us to understand the reasons for high incidences of epilepsy and seizures in elderly people. We look forward to controlling epileptic seizures via the treatment of primary diseases in the future. Keywords: epilepsy, seizures, causes, elderly